A Changing Climate for Science - Lewis, Sophie C. (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book offers a critical exploration of first-hand experiences of practicing climate scientists. It tackles the pivotal question of what, precisely, constitutes contemporary scientific practice. The author offers an insider's account of the experience of undertaking scientific training and of practicing as a climate scientist in order to examine the gulf between the way that science is perceived and pursued. Lewis delves into this discrepancy, drawing on personal experiences, recent scientific studies, extreme climatic events and political controversies. The book begins by considering the relevance of key concepts such as knowability, credibility, authority and objectivity to the practice of climate science. The following chapters argue that these concepts alone are limiting to our critical understanding climate science and climate change. The book then proposes a new view of scientific practice appropriate for diverse disciplines by arguing that concepts such as transparency and curiosity are equally important to scientific practice as the more familiar key concepts introduced at the start of the book. This book will appeal to climate scientists, social scientists and those interested in the challenges posed by future climate change. Sophie C. Lewis is a Senior Lecturer in the Fenner School of Environment and Society at The Australian National University (ANU), Australia. She is an investigator in the Centre of Excellence for Climate Systems Science and has published on past, present and future climate change and variability. .
Keywords: Social sciences.; Climate change.; Environmental policy.; Environmental sociology.; elektronické knihy; electronic books